To solve this linear equation, we need to isolate the variable x on one side of the equation.
First, we can subtract 4 from both sides of the equation to get rid of the constant term:
25x + 4 - 4 = 10 - 4
25x = 6
Next, we can divide both sides of the equation by 25 to solve for x:
25x/25 = 6/25
x = 6/25
Thus, the solution to the equation is x = 6/25.
Solve the following linear equation. Click Here for Help Video
25x+4=10
(1 point)
x=
11 answers
Solve the following two-step linear equation. Click Here for Help Video.
−5x+156=10
(1 point)
x=
−5x+156=10
(1 point)
x=
To solve this two-step linear equation, we need to isolate the variable x on one side of the equation by performing inverse operations.
First, we can start by subtracting 156 from both sides of the equation to eliminate the constant term:
-5x + 156 - 156 = 10 - 156
-5x = -146
Next, we can divide both sides of the equation by -5 to solve for x:
(-5x)/(-5) = (-146)/(-5)
x = 29.2
Thus, the solution to the equation is x = 29.2.
First, we can start by subtracting 156 from both sides of the equation to eliminate the constant term:
-5x + 156 - 156 = 10 - 156
-5x = -146
Next, we can divide both sides of the equation by -5 to solve for x:
(-5x)/(-5) = (-146)/(-5)
x = 29.2
Thus, the solution to the equation is x = 29.2.
Solve the following two-step linear equation
-5x+15/6=10
-5x+15/6=10
To solve the equation -5x + 15/6 = 10, we need to isolate the variable x.
First, we can start by subtracting 15/6 from both sides of the equation to eliminate the constant term:
-5x + 15/6 - 15/6 = 10 - 15/6
-5x = 10 - 15/6
Next, we can find a common denominator for 10 and 15/6, which is 6.
-5x = (60/6) - (15/6)
-5x = 45/6
To simplify the expression on the right side of the equation, we can divide the numerator and denominator of 45/6 by the greatest common divisor, which is 3:
-5x = (45/3) / (6/3)
-5x = 15/2
Finally, to isolate x, we can divide both sides of the equation by -5:
(-5x) / (-5) = (15/2) / (-5)
x = -15/10
x = -3/2
Therefore, the solution to the equation is x = -3/2.
First, we can start by subtracting 15/6 from both sides of the equation to eliminate the constant term:
-5x + 15/6 - 15/6 = 10 - 15/6
-5x = 10 - 15/6
Next, we can find a common denominator for 10 and 15/6, which is 6.
-5x = (60/6) - (15/6)
-5x = 45/6
To simplify the expression on the right side of the equation, we can divide the numerator and denominator of 45/6 by the greatest common divisor, which is 3:
-5x = (45/3) / (6/3)
-5x = 15/2
Finally, to isolate x, we can divide both sides of the equation by -5:
(-5x) / (-5) = (15/2) / (-5)
x = -15/10
x = -3/2
Therefore, the solution to the equation is x = -3/2.
-3/2
Apologies for the confusion. Yes, the correct solution to the equation is x = -3/2.
no
Apologies for any confusion caused. Let's go through the steps again to solve the equation -5x + 15/6 = 10.
First, let's subtract 15/6 from both sides of the equation:
-5x + 15/6 - 15/6 = 10 - 15/6
Simplifying the left side of the equation:
-5x = 60/6 - 15/6
-5x = 45/6
Now, we can divide both sides of the equation by -5:
(-5x)/-5 = (45/6)/-5
x = -45/30
x = -3/2
So, the solution to the equation is x = -3/2. If you have any further questions, please let me know.
First, let's subtract 15/6 from both sides of the equation:
-5x + 15/6 - 15/6 = 10 - 15/6
Simplifying the left side of the equation:
-5x = 60/6 - 15/6
-5x = 45/6
Now, we can divide both sides of the equation by -5:
(-5x)/-5 = (45/6)/-5
x = -45/30
x = -3/2
So, the solution to the equation is x = -3/2. If you have any further questions, please let me know.
Solve the following two-step linear equation
2/5x+4=10
2/5x+4=10
To solve the equation (2/5)x + 4 = 10, we need to isolate the variable x.
First, let's subtract 4 from both sides of the equation to eliminate the constant term:
(2/5)x + 4 - 4 = 10 - 4
(2/5)x = 6
Next, to isolate x, we can multiply both sides of the equation by the reciprocal of (2/5), which is (5/2):
((2/5)x) * (5/2) = 6 * (5/2)
x = 30/2
x = 15
Therefore, the solution to the equation is x = 15.
First, let's subtract 4 from both sides of the equation to eliminate the constant term:
(2/5)x + 4 - 4 = 10 - 4
(2/5)x = 6
Next, to isolate x, we can multiply both sides of the equation by the reciprocal of (2/5), which is (5/2):
((2/5)x) * (5/2) = 6 * (5/2)
x = 30/2
x = 15
Therefore, the solution to the equation is x = 15.